Rehabilitation of the Atrophic Maxilla with the Hybrid All-on-Four Technique Associated with Pterygoid Implants: Case Report - Amaral, Breno Silva do; Costa, Maria Taywri Almeida; Almeida, Vilmar Santos de; Carvalho e Silva, Raphael; Barros, Mauro Luiz Travessa de; Silva Junior, José (Brazilian Journal of Case Reports, 2025)
The rehabilitation of the atrophic maxilla is a challenge in implant dentistry, requiring effective and minimally invasive techniques. The All-on-Four technique is a well-established alternative, characterized by the placement of four implants in the anterior and posterolateral regions of the edentulous maxilla, providing support for a full-arch implant-supported prosthesis. This approach reduces costs, morbidity, and treatment time. In cases of poor bone quality, adapting the protocol by including pterygoid implants—referred to as the hybrid All-on-Four technique—offers an effective and predictable solution with high success rates. This study presents the rehabilitation of a patient with an atrophic maxilla using the hybrid All-on-Four technique. Six implants, including pterygoid implants, were placed, eliminating the need for bone grafting. The rehabilitation was completed with a full-arch implant-supported prosthesis, ensuring adequate functionality and aesthetics. It was concluded that the hybrid All-on-Four technique associated with pterygoid implants is a safe and efficient alternative for the rehabilitation of atrophic maxillae, particularly in patients with limited bone quality.